Effects of salt and low light intensity during the vegetative stage on susceptibility of rice to male sterility induced by chilling stress during the reproductive stage. (1st October 2016) - Koumoto, Takemasa; Saito, Naoko; Aoki, Naohiro; Iwasaki, Toshiki; Kawai, Shigenao; Yokoi, Shuji; Shimono, Hiroyuki
Abstract: We tested whether exposing rice plants to abiotic stress (salt or shade) during vegetative growth affects the chilling tolerance of reproductive organs, which is one of the most important traits for rice growing in a cool climate; we used two rice cultivars with different tolerance in two growing seasons. We divided the vegetative growth into three phases to clarify the most sensitive period: 7–22 days after transplanting (DAT), 23–38 DAT and 39–54 DAT. Chilling tolerance of the pre-stressed plants was based on the male sterility induced by low temperatures. Shade and salt stress during all three vegetative growth phases significantly reduced stomatal conductance. Shade decreased the specific leaf weight and the leaf sugar and starch contents, but salt had no significant effect, despite causing leaf damage. Low temperatures during the reproductive stage induced spikelet sterility in all plants, but the magnitude was greater in the salt- and shade-stressed plants of both cultivars, especially those stressed late during vegetative growth. The increased spikelet sterility caused by chilling was closely related to the reduction of the total spikelet number per panicle. This is the first study to show that salt and low light stress during vegetative growth increased the susceptibility of rice plants to chilling damage during panicle development.